Pengaturan Diet dan Pendidikan Gizi Meningkatkan Status Gizi dan Kesegaran Jasmani Atlet Sepakbola: Diet Combined with Nutrition Education Improve Nutritional Status and Physical Fitness of Football Athletes - Hesti Permatasari; Galeh Septiar Pontang (JURNAL GIZI DAN KESEHATAN, 2023)
Excellent physical fitness and optimal nutritional status are conditions for an athlete to perform optimally. Proper diet combined with nutrition education program are supposed to support the achievements of athletes in addition to the scheduled training program. This study aimed to identify the effect of diet combined with nutrition education on the nutritional status and physical fitness football athletes. The study was designed with the pre-post test control group design. The population was the students of the football academy in Semarang, 14-18 years old. There were 60 subjects selected by purposive technic sampling and divided into two (2) groups: dietary pattern arranged group and control group. Diet was given for 3 weeks to the treatment group, both groups got nutrition education. The nutritional status was measured with body mass index (BMI), lean body mass (Bioelectrical Impedance Analyzer (BIA)), hemoglobin (Hb) (cyanmethemoglobin). Physical fitness was analyzed using the methods of Asian Committee on the Standardization of Physical Fitness Test (ACSPFT). Data of the study was analized with independent t-test, paired t-test, Mann Whitney, Wilcoxon and General Linera Model. There was an increased IMT in the treatment group (0.26 kg/m2) higher than the control group (0.02 kg/m2) p = 0.0001, lean body mass increased in the treatment groups(1.57%), while in the control group it decreased (0.12%) p = 0.0001, score of ACSPFT in treatment groups (116.27) was higher than in the control group (3.47) before and after controlled for resting pulse rate p = 0.0001. Nutritional status and physical fitness have improved by diet combined with nutrition education in football athletes. ABSTRAK Syarat yang penting dipenuhi atlet untuk berprestasi adalah kesegaran jasmani dan status gizi optimal. Pengaturan diit atlet disertai pendidikan gizi dapat dijadikan program penunjang agar atlet berprestasi. Penelitian bertujuan menganalisis pengaruh pengaturan diit atlet disertai pendidikan gizi terhadap status gizi dan kesegaran jasmani atlet sepak bola. Penelitian berdesain pre-post test control group dengan 60 subjek dipilih secara purposif dan dibagi 2 kelompok yaitu kelompok kontrol dan perlakuan. Tempat penelitian adalah salah satu akademi sepak bola di Kabupaten Semarang dengan kelompok usia 14-18 tahun. Kelompok perlakuan diberikan pengaturan diit atlet sesuai kebutuhan berdasarkan usia dan aktivitas selama 3 minggu. Pendidikan gizi diberikan kepada semua kelompok. Penilaian status gizi menggunakan Indeks Massa Tubuh (IMT), komposisi lean body mass (Bioelectrical Impedance Analyzer (BIA), dan kadar hemoglobin (cyanmethemoglobin). Penilaian kesegaran jasmani menggunakan metode Asian Committee on the Standarduzation of Physical Fitness Test (ACSPFT). Data dianalisis menggunakan independent t-test, paired t-test, Mann Whitney, Wilcoxon dan General Linear Model. IMT kelompok perlakuan (0,26±0,42kg/m2) meningkat lebih tinggi dibandingkan kelompok kontrol (0,02±0,38kg/m2) dengan nilai p=0,0001. Kelompok perlakuan mengalami peningkatan lean body mass (1,57±1,34%), sebaliknya kelompok kontrol menurun  (0,12±0,57%) (p=0,0001). Skor ACSPFT kelompok perlakuan (116,27±17,31) meningkat lebih tinggi dibandingkan kelompok kontrol (3,47±23,27) sebelum maupun setelah dikontrol denyut nadi istirahat (p=0,0001). Pengaturan diit atlet disertai pendidikan gizi dapat meningkatkan status gizi dan kesegaran jasmani atlet sepak bola.